DEPICTION OF MARGINALIZATION AND UNSETTLEMENT IN FOREIGN LAND AS DEPICTED BY JAEL SILLIMAN IN HER SELECT NOVELS - VYAS, ANKITA; AGRAWAL, SHUCHI (International Journal of Psychosocial Rehabilitation, 2020)
Jews are settled in many countries like America, Middle East or even in India; wherever they have settled down, they happen to be in minority. The Baghdadi Jews had come to India to settle down and are marginalized as only a handful of them exist in the country. This paper is an attempt to throw light on the problems that these settlers have felt in the country like India. Problems of assimilation and forward moving leaving behind their culture and accept the rules of new society seems very difficult and need to be reflected upon by everyone who is a part and parcel of this society.